(3caGjI GddHjH aj GdJhbjJ HYed GdfSHI hGdLjhHs - (3YHO GdSdGe Hf CMeO Hf RGchQs ((3JZQ WfLI s)
(3ChdgG (B:s
(3GdMeO hHYO , ajbhd gPg QSGdI eNJUQI ai Yde GdChbGJ ai GdLjhH hGdCYOGO jJhUd HgG SQjYkG Edi eYQaI ChbGJ GdYHGOGJ s
(3BNQgG (B:s
(3hEf cGf deWGdY GdchcH agh GdeGVi HYOg hEf JSGhjG agh fUa Gddjd hgfG GfJgi GdebUhO HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B201 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs